The Effect of Human Resource Practices on Hotel Performance during Crisis: A Case Study of Star-Rated Hotels in Mombasa, Kenya - Mukolwe, Eunice; Rotich, Dorothy; Mapelu, Isabela; Ipara, Hellen (European Journal of Human Resource, 2023)
Purpose: Star-rated hotels play a pivotal role in the global economy, contributing significantly to international tourism, job creation, and fostering cross-cultural exchanges. These establishments are luxurious havens and symbols of excellence and diplomacy, promoting economic growth and development, attracting foreign investment, and serving as ambassadors of local culture. In Kenya, star-rated hotels are essential contributors to the national economy, promoting sustainability and wildlife conservation. While these hotels have traditionally thrived due to Kenya's vibrant tourism sector, the industry faces an ever-present threat of crises. Therefore, this study, anchored in the Resource-Based View (RBV) theory analyzed the effect of human resource practices on the performance of hotels in Mombasa County during crises. Methodology: This research employed a Covariance-Based Structural Equation Modeling (CB-SEM) approach, well-suited for assessing direct and indirect associations among observed and latent constructs. The study utilized an ex post facto research design to investigate the impact of specific Human Resource Management (HRM) practices on the performance of star-rated hotels in Mombasa County, Kenya, particularly during crises. Structured questionnaires were meticulously administered to 198 management staff members working within star-rated hotels in Mombasa County. This population was chosen due to its critical role in hotel operations, allowing the research to gain comprehensive insights into the relationships under examination. The response rate, approximately 90%, was considered practical and representative of questionnaire-based research. Data were analyzed using descriptive and inferential analysis techniques and presented in tabular format. Findings: The study indicated that Talent Retention and Training exhibited a statistically significant positive effect on hotel performance, with a substantial path coefficient of 0.619. Crisis Communication and Leadership also contributed significantly to hotel performance, showcasing a positive and statistically significant path coefficient of 0.355. On the other hand, Resource Management and Adaptability did not exhibit a statistically significant direct relationship with hotel performance, as indicated by a non-significant path coefficient (p = 0.607). The robust positive relationships discovered between Talent Retention and Training, Crisis Communication and Leadership, and hotel performance align harmoniously with previous research findings. These results underscore the critical roles these factors play within the hospitality industry. Investments in talent management and effective crisis management strategies are vital for a hotel's success. The non-significant relationship between Resource Management and Adaptability and hotel performance challenges conventional wisdom but emphasizes the importance of considering the specific contextual nuances. Recommendations: In conclusion, the study demonstrates that Talent Retention and Training, as well as Crisis Communication and Leadership, significantly contribute to the performance of star-rated hotels in Mombasa County, Kenya. These findings underline the need for hoteliers to prioritize investments in talent management, crisis management, and leadership skills. While the relationship between resource management, adaptability, and hotel performance appears more complex, further research is required to unearth any potential indirect effects or contextual nuances.